2003
DOI: 10.1124/jpet.103.052597
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Olanzapine, Risperidone, and Quetiapine on Ionotropic Glutamate Receptor Types: Implications for Antipsychotic Drug Treatment

Abstract: Levels of ionotropic glutamate (Glu) N-methyl-D-aspartate (NMDA),␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA), and kainic acid (KA) receptors in rat forebrain regions were compared by quantitative in vitro receptor autoradiography after continuous treatment for 28 days with the atypical antipsychotics olanzapine, risperidone, and quetiapine, or vehicle controls. All three treatments significantly decreased NMDA binding in caudate-putamen (CPu; by 30, 34, and 26%, respectively) but increased AMPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
209
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(247 citation statements)
references
References 47 publications
38
209
0
Order By: Relevance
“…This result confirmed previous reports that both short-term and chronic olanzapine treatment did not affect D 2 R bindings in the PFC, CPu and NAc (Kusumi et al, 2000, Han et al, 2009a. Similarly it has been reported that SGAs with lower affinity to D 2 R such as clozapine and quetiapine did not affect D 2 R bindings, while antipsychotics with high D 2 R affinity such as haloperidol, chlorpromazine and risperidone have been reported to increase D 2 R bindings (Tarazi et al, 1997, Kusumi et al, 2000, Tarazi et al, 2001). These results are consistent with a PET study showing that olanzapine had a lower D 2 R blockade compared to haloperidol in schizophrenia patients (Xiberas et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…This result confirmed previous reports that both short-term and chronic olanzapine treatment did not affect D 2 R bindings in the PFC, CPu and NAc (Kusumi et al, 2000, Han et al, 2009a. Similarly it has been reported that SGAs with lower affinity to D 2 R such as clozapine and quetiapine did not affect D 2 R bindings, while antipsychotics with high D 2 R affinity such as haloperidol, chlorpromazine and risperidone have been reported to increase D 2 R bindings (Tarazi et al, 1997, Kusumi et al, 2000, Tarazi et al, 2001). These results are consistent with a PET study showing that olanzapine had a lower D 2 R blockade compared to haloperidol in schizophrenia patients (Xiberas et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…180 It has been suggested that NMDA may mediate, at least partially, the activity of antipsychotic drugs, in particular of olanzapine and risperidone. 184,185 The pharmacogenetics of the glutamatergic system remains comparatively understudied, and no clear associations have been established between antipsychotic treatment and glutamate variants. GRM3 genotypes were associated with negative symptom improvement after treatment in a small sample of Caucasian patients.…”
Section: Pharmacodynamic Factorsmentioning
confidence: 99%
“…81 Antipsychotic drugs can modify GABA and glutamate system elements, including GABA A receptor, extracellular GABA levels and expression, glutamate transporters, 82 and neuregulin-1 (which regulates the expression of NMDA and GABA A receptors), 83 as well as ionotropic and metabotropic glutamate receptors. 84,85 Interestingly, atypical antipsychotics differ from the typical ones in their effect on the GABA system, including hippocampal and cortical GABA A receptor density, 86 GABA transporter expression, 87 and GABA transporter levels. 88 Mechanisms that may mediate drug-induced modification of the GABA system include inhibition of dopamine innervations on GABA and glutamate neurons, activation of PKC anchored to Rack1 (which then phosphorylates GABA A receptor), 89 and increase in brain levels of allopregnanolone, a potent positive allosteric modulator of GABA at the GABA A receptor.…”
Section: Clinical Relevancementioning
confidence: 99%